2020
DOI: 10.1039/d0rp00006j
|View full text |Cite
|
Sign up to set email alerts
|

Impact of arithmetic automaticity on students' success in second-semester general chemistry

Abstract: Completion of a first-semester chemistry (Chem I) course lays the foundation for understanding second-semester chemistry (Chem II) topics. The purpose of this study is to evaluate the influence of basic arithmetic skills on students’ Chem II success in understanding mathematics-grounded concepts (e.g., solutions and aqueous reactions, kinetics, equilibrium, acids and bases, solubility and equilibria, thermodynamics, electrochemistry, and nuclear chemistry). Previous studies suggest a strong correlation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Except for Chem I-on students (Figure 1), there is a slight bump in course average for the students who work 1-10 h/week. There was a similar improvement seen in the recently accepted paper by the NSA team on Chem II students [9]. The most obvious divide is the downfall of Chem II students when on/off semesters are combined; with a successful class average being over 69.5%, note that only those who do not work or only work 1-10 h/week successfully complete the courses.…”
Section: Indicators Of Successful Performancesupporting
confidence: 57%
See 2 more Smart Citations
“…Except for Chem I-on students (Figure 1), there is a slight bump in course average for the students who work 1-10 h/week. There was a similar improvement seen in the recently accepted paper by the NSA team on Chem II students [9]. The most obvious divide is the downfall of Chem II students when on/off semesters are combined; with a successful class average being over 69.5%, note that only those who do not work or only work 1-10 h/week successfully complete the courses.…”
Section: Indicators Of Successful Performancesupporting
confidence: 57%
“…Regardless of how confident in career choice they report, their preparation for their courses (i.e., their prior knowledge) is of upmost importance to having a more successful outcome. When they enter with low automaticity ability (what they can do without a calculator), they lack the mental-math skills that provide them with the ability to answer and complete problems they are likely to encounter in their general chemistry studies without struggling with the basic arithmetic skills as identified by the MUST, an excellent known predictor of course outcomes [6,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some students self-identified as non-binary for gender, this group was too small to report on while maintaining confidentiality. Previous studies by the Networking for Science Advancement (NSA) team have reported that students' automaticity ability (what can be done without the aid of a calculating device), as measured by an easily administered diagnostic test named the MUST (Math-Up Skills Test), correlates well with students' success in general chemistry courses (Albaladejo et al, 2018;Mamiya et al, in press;Petros et al, 2017;Powell et al, 2020;Villalta-Cerdas et al, in press;Weber et al, 2020;Williamson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has a very large Cohen's d effect size of 1.43 and 1.20 for Chem I and II, respectively. The NSA Team has published the advantages of using the calculator-free MUST assessment to identify students early in the semester who potentially might struggle with the content of Chem I(Williamson et al, 2020) and Chem II(Powell et al, 2020). Items on the open-response MUSTs were scored on a binary scale as either correct (1) or incorrect (0).…”
mentioning
confidence: 99%